Negotiating agricultural trade in a new policy environment - Glauber, Joseph W. (International Food Policy Research Institute, 2019)
The challenges to meeting the growing global food demand—population and income growth and supply uncertainties complicated by climate change, environmental pressures, and water scarcity—all point to the increasing importance of trade and the need for a more, not less, open trading system. Growth in agricultural trade has been facilitated in part through the rules-based system established under the World Trade Organization (WTO), particularly the Uruguay Round Agreement on Agriculture (AoA). The AoA was implemented in 1995 and brought substantial discipline to the areas of market access, domestic support, and export competition. However, progress since the Uruguay Round has been limited. While the Doha Development Agenda (DDA) was launched with much anticipation in 2001, members failed to reach agreement in July 2008 and the trade agenda in Geneva has since advanced slowly. Despite the best efforts of many, the negotiating intensity seen in late 2007 and 2008 has largely dissipated, in part due to the global recession and the inevitable changes in governments that sometime shift the focus of negotiations. Serious efforts were made to renew the negotiations, but in the end, members have had to be content with harvesting the low-hanging fruit, such as trade facilitation and export competition. Although there have been significant accomplishments, they represent but a small portion of what was on the table during the DDA negotiations. In addition, negotiated settlements on the tougher issues, such as market access and domestic support, have become more difficult to obtain in isolation. The recent experience at the WTO’s Eleventh Ministerial Conference in Buenos Aires highlights the difficulties of reaching a negotiated settlement on domestic support in isolation from, say, market access. Given the increasing importance of trade in addressing food security needs and its critical role in efforts to eliminate malnutrition and hunger by 2030, achieving further progress in the liberalization of world trade is of paramount importance.